2020
DOI: 10.1159/000509386
|View full text |Cite
|
Sign up to set email alerts
|

Skull Base Chordomas and Chondrosarcomas

Abstract: Skull base chordomas account for less than 0.2% and chondrosarcomas for less than 0.15% of all intracranial tumors. Although their clinical and imaging presentations are similar, they derive from different origins. Chordomas arise from embryonic remnants of the primitive notochord and chondrosarcomas from primitive mesenchymal cells or from the embryonic rest of the cranial cartilaginous matrix. Both entities are characterized by infiltration and destruction of the surrounding bone and soft tissue and a high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 123 publications
3
89
0
Order By: Relevance
“…It is well established that complete resection of skull base chordomas and chondrosarcomas is difficult, and, even in cases with good macroscopic clearance, there may be microscopic tumour cells left behind. This is demonstrated by the high recurrence rate in our series, particularly in the chordoma cohort, and this is consistent with current literature [17]. As a result, many patients can be offered higher dose adjuvant radiotherapy which provided the best chance of local control.…”
Section: Discussionsupporting
confidence: 92%
“…It is well established that complete resection of skull base chordomas and chondrosarcomas is difficult, and, even in cases with good macroscopic clearance, there may be microscopic tumour cells left behind. This is demonstrated by the high recurrence rate in our series, particularly in the chordoma cohort, and this is consistent with current literature [17]. As a result, many patients can be offered higher dose adjuvant radiotherapy which provided the best chance of local control.…”
Section: Discussionsupporting
confidence: 92%
“…As described by Feuvret et al [ 36 ], primary SBCs may also invade the anterior fossa, mostly causing vision impairment and hypopituitarism by directly compressing the optic apparatus or the pituitary stalk. However, such symptoms are non-specific and may also occur in patients with skull base chordomas and other sarcomas [ 8 , 56 , 57 ]. Likewise, radiological features of chordomas and SBCs may overlap, with similar localization and bone destructive patterns [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…While low-grade SBCs may be indolent and slow-growing, poorly differentiated neoplasms are highly invasive, destructive, and may metastasize. Symptoms derive from the direct compression of cranial nerves and neurovascular structures at the base of the skull, with headache and diplopia being the most frequent [ 5 , 8 ]. Computer tomography (CT) scans can evaluate bone invasion and destruction, but magnetic resonance imaging (MRI) provides better delineation of soft tissue involvement in skull base chondromas [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chordomas are rare, malignant, locally destructive, slowly growing bone tumors that show an invasive growth behavior; prognosis is poor with a median survival of seven years after diagnosis. Current treatment concepts include surgical en-bloc resection with negative margins and high-dose radiation therapy as well as chemotherapy for the extremely rare dedifferentiated chordomas 1 , 2 . Several authors have suggested an interaction between hepatocyte growth factor (HGF)/cMET and epidermal growth factor receptor (EGFR) signalling 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%